ANALISIS PEMANFAATAN SEARCH ENGINE OPTIMIZATION DALAM MENINGKATKAN PENJUALAN PRODUK UKM DI PASAR INTERNASIONAL (Studi Kasus Pada CV. Ayung Sportindo) - Ahmad Fauzan Satibi; Suharyono Suharyono; Yusri Abdillah (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
This study aims to determine the utilization of search engine optimization in increasing sales of UKM products in the International Market. This research uses descriptive qualitative method using case study approach. This study focuses on the application of marketing by utilizing search engine optimization in the development and improvement of product sales in the international market. This research is done in the office as well as the production of CV. Ayung Sportindo with its website